Keanekaragaman Jenis Ikan Karang di Zona Intertidal Pantai Kondang Merak - Binsasi, Yeremias; M.Y. Hanoe, Emanuel (BULLET : Jurnal Multidisiplin Ilmu, 2023)
Coral fish is a group of animals associated with coral reefs. Reef fish can easily be found in various microhabitats on coral reefs. This study aims to determine the diversity of reef fish species in the intertidal zone of Kondang Merak beach. Observations were made using the underwater visual census method. Observations were made by following a 100 m long transect line with a visibility of 2.5 m to the left and right. The research location points consist of 6 stations at a depth of 1-3 m with a distance of 100 m each station. Based on the results of the study, it can be concluded that there are 29 species of reef fish in the intertidal zone of the Kondang Merak coast, belonging to 15 families, and a category of high species diversity with a diversity index value of 3.239.